Reader digest association 101 ways to improve your memory (London, 2005)
Enhance your memory with 1,000 full-color photographs, illustrations, diagrams and puzzles to keep your mental juices flowing! 101 WAYS TO IMPROVE YOUR MEMORY features easy and entertaining ways to: * Learn tips and tricks to remember new facts ? Test your memorization skills * Find out which senses you use the most * Discover why the brain forgets things. Get ready to boost your memory with more than 500 puzzles to give your memory muscle the workout it deserves.
Keywords: "Memory, Memory-Testing"